Compatibility Analysis of A Novel Antidepressant with Different Excipients in Solid Dosage Forms and in Some Binary Mixtures - Jain, Suman; Vaidya, Leena; Sharma, Radha (Asian Journal of Chemistry, 2010)
The present paper compared thermodynamic data on a novel antidepressant's (venlafaxine hydrochloride) melting and vapourization processes with those found for several solid binary mixtures and in some commercially available venlafaxine hydrochloride based dosage forms. No universally accepted protocol is available for evaluating the compatibility of drug with different excipients. Some of the reported methods have poor predictive values and few of them are labour intensive and time consuming. Differential scanning calorimetry was used to assess the compatibility between venlafaxine hydrochloride and some excipients in several of more commercially available pharmaceutical formulations and in solid binary mixtures. This technique allows a rapid evaluation of possible incompatibilities by revealing changes in appearance, shift or disappearance of melting or other exothermic processes and/or variations in the corresponding enthalpies of reaction. By the comparison of thermal, thermodynamic and kinetic values for pure venlafaxine hydrochloride and venlafaxine hydrochloride containing in dosage forms and in binary mixtures only slight differences were observed with the opadry yellow and one formulation (D-3) formulation. Differential scanning calorimetry traces of pure venlafaxine hydrochloride showed a sharp endothermic peak at 217 ºC corresponding to its melting point. In case of binary mixtures and formulations containing large amount of excipients showed a slight change in endoth-ermic peak. Present study had demonstrated the successful utilization of technique of differential scanning calorimetry to assess the compatibility of venlafaxine hydrochloride with the excipients. Based on the results of differential scanning calorimetry majority of excipients showed compatibility with venlafaxine hydrochloride except opadry yellow. So these excipients can be used to develop novel formulation of venlafaxine hydrochloride.